AB0246 Genetic variability with toll-like receptor 10 affects susceptibility to rheumatoid arthritis and modulates response to biological treatment. (12th June 2018) - Wysoczanska, B.; Swierkot, J.; Puchala, M.; Kolossa, K.; Jeka, S.; Wiland, P.; Bogunia-Kubik, K.
Abstract : Background: Genetic variability in Toll-like receptor 10 (TLR10) may change the balance between pro- and anti-inflammatory responses, and hence modulate the susceptibility to infection and to autoimmune disease including rheumatoid arthritis (RA). Objectives: Therefore we aimed to assess the possible associations of the TLR10 genetic variants with RA susceptibility and/or response to treatment Methods: TLR10 gene (rs 11096957, N241H, A>C) polymorphism was genotyped by LightSNiP assay in 303 RA patients (237F/66M) and in 140 healthy individuals from Polish population. Results: RA patients with the AC genotype showed predisposition to disease development [OR 1.99 (1.32–3.01); p=0.001], while the AA homozygosity seemed to play a protective role [OR 0.63 (0.42–0.95); p=0.034]. Response to treatment with TNF-alpha inhibitors was more effective after 6 months as compared to 3 months (p=0.001), especially in female patients (p=0.05). Women carrying the A allele responded better to treatment after 6 months of anti-TNF treatment as compared to those with the CC genotype (p=0.053). Response to biological treatment was more effective in patients with low stage of disease (p=0, 01), with rheumatoid factor (RF) positivity (p=0.01) and with double positivity against cytrulinated (CCP) protein and RF (p=0.003). RF-positive patients (especially women, p=0.001) characterised with a higher degree of the disease as compared to RF-negative cases (p=0.01). Men had a higher activity of the disease before anti-TNF treatment (p=0.05), therefore the remission of the disease was more common in women (p=0.04). Conclusions: These results imply that the TLR10 polymorphism has an important role in RA and may potentially influence risk of the disease and effectiveness of biological treatment. Acknowledgements: Supported by the National Science Centre grant No. 2016/ 21/B/NZ5/01901. Disclosure of Interest: None declared